A review of science teaching approaches for equity focusing on race, class, and religion from the perspectives of Freire's and Arendt's theories of education - Rüschenpöhler, Lilith (Science education (Salem, Mass.), 2024)
This paper presents a literature review of science teaching approaches that seek to support equity in science classrooms, focusing on marginalization based on (i) race/ethnicity, (ii) social class/socioeconomic background, and (iii) religion. Considered were approaches that science teachers can use in science classes in secondary schools. They were analyzed and discussed against the backdrop of critical pedagogy by Paulo Freire and the educational theory by Hannah Arendt, which constitutes a novelty in science education research. The review used meta interpretation combined with systematic searches in the ERIC database. It is, thus, limited to works published in English. A total of 930 articles (2013–2021) were identified out of which 64 were fully analyzed. The analysis shows that most approaches strive to provide more equal access to the existing science knowledge and structures of the community. This corresponds to the introduction to the “old world” in a conservative interpretation of Arendt's term. I argue that in addition, it is necessary to employ a more radical interpretation of the “old world” as fundamentally plural which is done in translanguaging and grappling with racism. Further, the transformative nature of science education needs to be strengthened in terms of Freire's critical pedagogy and Arendt's concept of natality. This means allowing students to become aware of oppressive structures to induce change. Only youth participatory science, youth participatory action research, and grappling with racism explicitly aim for this. This shows that nuanced perspectives on equity in science education are needed.